Analysis of production and economic losses of cash crops under variable drought: A case study from Punjab province of Pakistan. (1st February 2023) - Rahman, Khalil Ur; Hussain, Anwar; Ejaz, Nuaman; Shang, Songhao; Balkhair, Khaled S.; Jan Khan, Kaleem Ullah; Khan, Mahmood Alam; Rehman, Naeem Ur
Abstract: The current study assesses the impact of drought severity on major cash crops, i.e., wheat and rice, and monetizes crop yield losses at a disaggregated level under variable drought conditions in Punjab province, Pakistan. Standardized Precipitation Evapotranspiration Index (SPEI) is used to calculate drought severity in Kharif (May–October) and Rabi (November–April) during 2000–2020. SPEI, with a spatial resolution of 0.25° × 0.25°, is calculated using Weighted Averaged Least Square-based merged satellite precipitation dataset and temperature data interpolated from ground measurement using the topographically and climatically informed interpolation method. Results show severe drought events occurred in 2000–2003, 2006–2008, 2013, 2017, and 2018. The severity of drought increases from northern Punjab to southern Punjab, where temperature is the key factor for drought onset. Layyah, D.G. Khan, Rajanpur, Bahawalpur, Bahawalnagar, Rahim Yar Khan, Muzaffargarh, Multan, Faisalabad, Jhang, and Lahore districts are prone to severe drought. Results showed highest wheat losses in Attock, Bahawalpur, Chakwal, Pakpattan, and Sargodha. During the severe drought period (1998–2003), wheat yield losses in Bahawalpur, Attock, and Chakwal were 1.665 t/ha, 1.114 t/ha, and 1.028 t/ha, respectively. Similarly, highest loss in rice yield (0.67 t/ha) was observed in Mandi Baha Uddin. The monetary losses under variable drought severity are calculated using least square multiple linear regression. SPEI coefficients are estimated for all districts while controlling for precipitation and maximum/minimum temperatures. Monetary losses are proportional to SPEI coefficient, i.e., higher the SPEI coefficient, higher the production losses for wheat and rice. The highest monetary losses are observed in southern Punjab, especially in D. G Khan. Results of regression models revealed that drought significantly contributed to crop yield losses. Highlights: We assessed the impact of meteorological drought on cash crops across Punjab, Pakistan. Monetary losses are estimated using a multiple linear regression model. Output losses increase with drought severity, especially in southern Punjab. The monetary losses are proportional to SPEI coefficients. Drought is one of the dominant factors in yield reduction in Punjab.